INDICADORES DE PARTICIPAÇÃO NO PROJETO DE EXTENSÃO PUC MAIS IDADE – BETIM DURANTE O REGIME LETIVO REMOTO. - Martins, Nayara Gonçalves; Carmo, Mariana Pereira de Souza; Silva, Dayane Jhenifer Ribeiro; Amorim, Maria Clara Botelho Vieira; Balbi, Sabrina Oliveira Viana (Sinapse Múltipla, 2020)